Pricing and investment in public enterprise - Institute for Public Enterprise (New Delhi: Oxford & IBH, 1974)
This volume includes the deliberations of the seminars held by the Institute of Public Enterprise in Bangalore in September 1969 and in New Delhi in January 1970, along with the working papers on pricing and investment in Public enterprise.
Includes index
obn 25/01/2019
Loans
Keywords: Prices; Pricing; Public enterprises; Government business enterprises---Finance; India